Strategies of prosociality: Comparing Nordic and Slavonic altruism toward Ukrainian refugees - Larsen, Mads; Witoszek, Nina (Frontiers in Psychology, 2023)
Nordic high-trust societies are underpinned by prosociality, a term denoting cooperation and working for the good of others. State-funded voluntarism provides opportunities for altruism that appears to contribute to the Nordics’ exceptional level of well-being. Altruists are rewarded by a warm, lasting affect that enhances personal well-being, thus motivating further prosociality. Humanity’s evolutionary past coded into us a desire to strengthen our community by helping those in need—a biocultural drive that is corrupted when authoritarian regimes enforce unselfish behavior on disempowered populations. Such coercive altruism has a line of adverse long-term consequences for communal functionality and individual flourishing. Our study examines how sociocultural context influences people’s prosocial strategies, and how sharing insights and practices from democratic and authoritarian traditions can lead to new, revitalized forms of altruism. Our in-depth interviews (n = 32) of Nordic and Slavonic helpers of Ukrainian refugees in Norway (1) illuminate the impact of culture and memory on altruistic practices, (2) define points of tension between systemic and anti-systemic modes of prosociality, and (3) identify cross-cultural interactions that generate trust, well-being, and social innovation. The post-communist experience of the Slavonic informants motivated anti-systemic altruism, which highlights spontaneity, improvisation, and occasional rule breaking. Norwegian systemic altruism is based on trust, efficacy, and rule-following. Our evolutionary approach to cultural psychology substantiates how important it is for development and immigration policies to align our knowledge of human nature with insights into the workings of cultural legacies. A better understanding of the biocultural mainsprings of altruism could be of crucial importance in our era of reemerging authoritarianism and increasing migration.